Avaliação de derivados de lactonas macrocíclicas contra infestações naturais de Boophilus microplus (Canestrini, 1887) (Acari: ixodidae), Dermatobia hominis (Linnaeus Jr., 1781) (Diptera: cuterebridae) e de infecções por helmintos gastrintestinais, em bovinos de corte. - Vanderson Barcelos Rangel (2003)
The comparative efficacy of three applications of injectable formulations of one or two brands of ivermectin 1% (IVMa and IVMb) LA 1% ivermectin (IVMc), doramectin (DRM) and an experimental endectocid product (ESP), compared with an untreated control group, was assessed against the parasites Boophilus microplus larvae of Dermatobia hominis and gastrointestinal helminths in beef cattle Canchim naturally infested. Seventy-nine animals were divided according to weight in four groups of 16 animals and one of 15 animals each: T1 - control, T2 - IVMa, T3 - or PEE IVMb, T4 - T5 and IVMc - DRM. The animals were subjected to counting of ectoparasites, feces, and passing on day 0 and every 28 days during the 252 days of experiment. Stool samples from each group were used in performing stool culture to determine the genera of nematodes involved. There were differences between the weights of the treated groups and untreated group, but no difference between the treated groups. The products studied were effective in controlling the Boophilus mocriplus abaliação until the fourth, fifth from the evaluation there was an increase in infestations of all groups and was needed to make a control with acaricide.